2015
DOI: 10.1016/j.earlhumdev.2014.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Adult digit ratio (2D:4D) is not related to umbilical cord androgen or estrogen concentrations, their ratios or net bioactivity

Abstract: Our findings indicate that digit ratio is not related to fetal androgens or estrogens at late gestation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
62
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 55 publications
(94 reference statements)
6
62
3
Order By: Relevance
“…I reported on two studies of amniotic fluid [3,4] and four studies of umbilical cord blood [5,6,7,8]. Manning and Fink correctly pointed out that there are two additional studies relating to cord blood.…”
mentioning
confidence: 99%
“…I reported on two studies of amniotic fluid [3,4] and four studies of umbilical cord blood [5,6,7,8]. Manning and Fink correctly pointed out that there are two additional studies relating to cord blood.…”
mentioning
confidence: 99%
“…females with congenital adrenal hyperplasia) [19,20]. However, limitations of these approaches have been widely documented, with reports of poor correlations between 2D : 4D and more direct measures of the prenatal hormone environment [21,22], as well as concerns about the extent to which data from clinical populations can be extrapolated to the general population.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between prenatal testosterone (or T/E ratio) and the digit ratio seems to be valid based on both experimental studies on laboratory animals (Zheng & Cohn, 2011) and various indirect evidence on humans (Brown et al, 2002;Galis, Ten Broek, Van Dongen, & Wijnaendts, 2010;€ Okten et al, 2002;Ventura et al, 2013). Despite this major trend, it must be clearly stated that a number of studies found null or even contradictory results of sexual differences in the digit ratio or its supposed relationships, both in humans (Apicella, Tobolsky, Marlowe, & Miller, 2016;Buck, Williams, Hughes, & Acerini, 2003;Dressler & Voracek, 2011;Hickey et al, 2010;Hollier et al, 2015;O swie R cimska et al, 2012;Putz, Gaulin, Sporter, & McBurney, 2004) and nonhuman animals (Lilley et al, 2009). Our present study showed that this might be caused partly by insufficiently assessed individual level of ontogenetic changes.…”
Section: Discussionmentioning
confidence: 99%